Peningkatan Keterampilan Kader tentang Mom dan Baby’s Care: Perawatan Payudara dan Pijat Bayi (UIR PRESS, 2024)
Health cadres are an important party as a community driver to change attitudes and behavior to improve health and welfare, especially for mothers and children. The data obtained is based on the results of interviews in the Kemiling Community Health Center area with cadres, namely that almost 90% of mothers do not know how to care for their breasts, especially during the postpartum period and the majority of mothers who have babies and toddlers do not know how to massage babies and 100% are afraid to do baby massage. to her own baby. As a result of interviews with cadres, they asked for updates on how to perform breast care and increase their knowledge of skills related to baby massage because no training had been given to them regarding baby massage. Meanwhile, it is known that both breast care and healthy baby massage have many benefits for improving the health of mothers and children and have an impact on the quality of individuals in the future. The aim of this Community Service Activity is to increase cadres' knowledge and skills regarding breast care and baby massage so that they can pass this on to mothers and the community so they can do it independently. The PKM method directly trains cadres using 3 methods, namely lectures, questions and answers, demonstrations and re-demonstrations. Evaluation is carried out from pre-post test instruments and checklists. The conclusion was that cadres' knowledge and skills regarding Breast Care and Baby Massage increased.